Attributions on the Performance of the National Qualifying Examination for School Heads: An Exploratory Study - Galleposo, Gabriel T. (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2021)
There is a very limited number of studies on why majority of school heads who took the National Qualifying Examination for School Heads (NQESH) failed, thus the necessity to conduct this study. It explored the factors that influenced the ratings of NQESH through exploratory sequential mixed methods involving 102 school heads in the 1st Congressional District of Zamboanga Sibugay. The qualitative data gathered from 10 respondents through face-to-face interview and focus group discussion arrived at the factors that affected NQESH performance, namely: luck, ability, strong desire, physical state, task difficulty, emotional state, mental state, and effort. The quantitative data gathered from 92 respondents through a researcher-made survey instrument were subjected to Pearson Coefficient of Correlation, t-test and stepwise regression. It is concluded that the internal locus of control factors such as ability, effort, physical state, and NCBS-SH domains along with the external locus of control factors such as luck, and task difficulty, wield a significant influence in the NQESH performance. Educational attainment, level of management training attended, and marital status were also differentiating factors in NQESH performance. Based on the regression analyses results, NCBS-SH, management training, ability, and task difficulty are good predictors of NQESH performance. NCBS-SH competencies can improve and enhance school management ability. Dynamic professional development and more developed critical and analytical skills are definitely needed to pass the NQESH.